Efficacy of 5% tranexamic acid in melasma - Ramzan, Faisal; Malik, Khadija; Bashir, Bushra; Naseer, Zaeema; Shehzad, Atif; Malik, Lamees; Rashid, Tariq (Journal of Pakistan Association of Dermatologists, 2023)
Melasma is common acquired hyper -melanosis of sun-exposed skin, and is seen frequently in individuals with darker skin type thus causing considerable cosmetic disfigurement. The exact cause of melasma is unknown but multiple factors are implicated in its etiopathogenesis, mainly ultraviolet light exposure, pregnancy, iron deficiency and oral contraceptive use. Treatment of melasma has generally been difficult. Tranexamic acid has been used in dermatology for the improvement of melasma. Objective To determine the efficacy of topical 5% tranexamic acid cream in patients of melasma Material & Methods: Total 100 patients of either gender with clinical diagnosis of melasma were enrolled in the study after taking informed written consent. The demographic data was collected on a pre-designed proforma. Baseline modified MASI score was calculated and pictures were taken of all patients at baseline. The patients were advised to apply 5% topical tranexamic acid cream at night along with sunscreen during day time for 12 weeks daily. All patients were evaluated for improvement of melasma using percentage reduction in MASI score at the end of 12 weeks and pictures were also taken again Results The mean age of the patients was 29.23Â±6.58 years. Out of 100 patients, 81 were female and 19 were males with male to female ratio of 0.2:1. The mean percentage reduction of the modified MASI score at the end of 12 weeks was 41.43Â±14.56. Sixty three percent of patients had < 50% reduction while thirty seven percent had >50% reduction in modified MASI score after 12 weeks. In our study the efficacy was achieved in 37(37%) patients. Conclusion:This study concluded that the topical 5% tranexamic acid cream was effective in 37% of melasma patients in our study population (>50% reduction in baseline Modified MASI score) after 12 weeks.